Development of ready‐to‐reconstitute carrot pomace blended sweet corn porridge. Issue 2 (21st March 2023) - Nayi, Pratik; Kumar, Navneet; Chen, Ho‐Hsien
Abstract: The demand for the development of functional and nutrients‐rich products for boosting immunity is the prime focus of consumers. The carrot pomace, a potential by‐product of carrot juice, was used to develop fortified sweet corn porridge. Response surface methodologies used for the optimization process parameters, like, the proportion of carrot pomace (10–50 g/100 g), milk (50–250 mL/100 g), sugar (12–20 g/100 g), and cooking time (10–20 min) were selected for to assess the product quality parameters, like, color L *, a *, and b * value, pH, total soluble solids, ascorbic acid, reducing sugar, total sugar, moisture content, and ash content of carrot pomace‐fortified sweet corn porridge. The sweetness of sweet corn and carrot minimized the need for additional sugar, which is an essential part of the preparation of porridge. The R 2 value for the various models ranged from 0.7062 to 0.8739. The optimized sample based on a maximum value of ascorbic acid (20.19 mg/100 g) and overall acceptability (7.82) was finalized at 35 g carrot pomace, 100 mL milk, 16.00 g sugar, and 13 min cooking time of the final product. The optimized product was dehydrated, which can be stored for a longer duration and used after reconstitution. Abstract : (1) Functional and nutrients‐rich products for boosting immunity are the prime focus of consumers. (2) The carrot pomace, a potential byproduct of carrot juice, was used to develop fortified sweet corn porridge. (3) New functional food which may be useful for the industry and consumers due to minimal use of additional sweeteners.